Development of watermelon rind derived activated carbon/manganese ferrite nanocomposite for cleaner desalination by capacitive deionization. (1st November 2020) - Rambabu, K.; Bharath, G.; Hai, Abdul; Luo, Shaohong; Liao, Kin; Haija, Mohammad Abu; Banat, Fawzi; Naushad, Mu.
Abstract: Capacitive deionization (CDI) is one of the most efficient and emerging techniques for water desalination applications. This work reports the development, characterization and CDI studies of watermelon derived activated carbon (WMAC) and its MnFe2 O4 composite (WMAC/MnFe2 O4 ) for NaCl desalination. WMAC was prepared through single-step low-temperature pyrolysis by H3 PO4 activation. Facile synthesis of spinel MnFe2 O4 nanoparticles on WMAC surface was performed through the hydrothermal technique. Morphological, textural and physico/electro–chemical analysis showed the effect of MnFe2 O4 incorporation on WMAC. The nanocomposite possessed definite crystallites, low structural disorders and sufficient magnetization for electrochemical applications. Also, the nanocomposite was dominantly composed of mesopores with a specific surface area of 483 m 2 /g. The high specific capacitance value of 425 F/g (scan rate – 10 mV/s) along with better stability and low charge resistance, confirmed the suitability of WMAC/MnFe2 O4 as an efficient electrode material for CDI applications. NaCl removal studies using WMAC/MnFe2 O4 showed an electrosorption capacity of 29.7 mg/g for the nanocomposite, with rapid desalination and good recyclability. A plausible mechanism of salt adsorption and desorption is also presented. WMAC/MnF2 O4 exhibited significant application potential for the industrial desalination. Graphical abstract: Image 1 Highlights: WMAC and its MnFe2 O4 composite were developed as effective CDI electrode materials. High specific capacitance of 425 F/g was obtained for WMAC/MnFe2 O4 nanocomposite. High NaCl uptake capacity of 29.7 mg/g with rapid electrosorption rate & reusability. WMAC/MnFe2 O4 nanocomposite is a promising candidate for desalination in industries.